Filamentous fungus Paecilomyces variotii in feed for Rainbow trout (Oncorhynchus mykiss) - Dahlberg, Amanda (2019)
Aquaculture production has been increasing rapidly over the last few decades and therefore the amount of feed needed for the increasing production is also on the rise. Salmonids and other farmed carnivorous fish require high amount of protein in their diets, which is currently supplied mostly by fish meal or soy bean. Therefore, there is a need to identify other alternative sustainable protein sources, preferably those that are not grown on arable land or can be used directly for human consumption. Single cell protein are microorganisms such as fungi, bacteria, yeast and mould, that contain a high level of protein and can be grown on various substrates such as resi-dues from other industries. Filamentous fungus Paecilomyces variotii is a mould that can be grown on residues from the wood industry and is characterized by a high pro-tein content.